2000
DOI: 10.1161/01.atv.20.5.1354
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fibrin Network Conformation and Fibrin Fiber Diameter on Fibrinolysis Speed

Abstract: Abstract-Abnormal fibrin architecture is thought to be a determinant factor of hypofibrinolysis. However, because of the lack of structural knowledge of the process of fibrin digestion, relationships between fibrin architecture and hypofibrinolysis remain controversial. To elucidate further structural and dynamic changes occurring during fibrinolysis, cross-linked plasma fibrin was labeled with colloidal gold particles, and fibrinolysis was followed by confocal microscopy. Morphological changes were characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
437
3
6

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 456 publications
(486 citation statements)
references
References 28 publications
(35 reference statements)
40
437
3
6
Order By: Relevance
“…Cross-linking of fibronectin to fibrin has been shown to have no effect on clot rigidity, however those clots were denser, with smaller pores [37]. A more recent study by Ramanathan et al, in a purified system in the absence of FXIII, showed that fibronectin increases the initial rate of fibrin polymerisation, leading to the formation of denser clots [38], thought to be more resistant to fibrinolysis [39].…”
Section: Other Cross-linking To Fibrinmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-linking of fibronectin to fibrin has been shown to have no effect on clot rigidity, however those clots were denser, with smaller pores [37]. A more recent study by Ramanathan et al, in a purified system in the absence of FXIII, showed that fibronectin increases the initial rate of fibrin polymerisation, leading to the formation of denser clots [38], thought to be more resistant to fibrinolysis [39].…”
Section: Other Cross-linking To Fibrinmentioning
confidence: 99%
“…Ligation of thrombospondin-1 within the fibrin clot was found to reduce the lag-time and lead to the formation of denser clots containing thinner fibres, in a dose-dependent manner [41], rendering them more resistant to fibrinolysis [39].…”
Section: Other Cross-linking To Fibrinmentioning
confidence: 99%
“…Assessment of the structure of the fibrin clot itself in relation to atherothrombotic disease development has revealed its structure to be heterogeneous, being influenced by genetic and environmental factors [14]. Clinical studies have reported an association between clot structure and the development of premature coronary heart disease [15]; patients suffering a myocardial infarction before the age of 45 years formed clots with a denser, less permeable structure than healthy control subjects [15], a structural change that may contribute to atherothrombotic risk by increasing resistance to fibrinolysis [16].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the structure of the fibrin clot in relation to diabetes has revealed that fibrin clots formed from the plasma of subjects with type 1 diabetes have a denser structure, with smaller intrinsic pores than those formed by healthy control subjects [17,18], a feature that has been shown to enhance a clot's resistance to fibrinolysis [16,19]. However, the mechanism(s) by which fibrin clot structure is altered in type 1 diabetes are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Although individual thinner fibers lyse more easily [30] a dense network of thin fibrin fibers are more resilient to lysis than thick fibers arranged in a more dispersed configuration, regardless of the quantity of the lytic agent [31]. Since both hormones decrease the 22 fibrin fiber diameter it could be assumed that in turn this would decrease the local enhancement and acceleration of fibrinolysis [31]. However, turbidimetric analysis indicated that both 17β-Estradiol and Progesterone decreased the CLT, although only significantly for 17β-Estradiol at concentrations between 140 -300 pg.mL -1 .…”
Section: Discussionmentioning
confidence: 99%